2015
DOI: 10.1590/s1413-70542015000100009
|View full text |Cite
|
Sign up to set email alerts
|

CRAMBE CAKE (Crambe abyssinica hochst) ON LAMB DIETS

Abstract: The use of alternative feedstuffs in animal diet, such as residues derived from the biodiesel production aims to increase productivity and reduce costs in animal production. Them aim of this study was to evaluate the substitution effect of 0, 22, 44 and 64% of soybean meal protein by Crambe cake (Crambe abyssinica Hochst) protein in lamb diet. In the in vivo experiment, 20 lambs were used and evaluated the apparent digestibility, nitrogen balance and voluntary DM intake. The replacement of the protein resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
0
18
0
3
Order By: Relevance
“…From the crambe extraction process, by-products (crushed, meal or cakes) are generated with high protein content and great potential for use in ruminant feed to replace traditional protein sources such as soybean meal and cotton (Canova et al 2015;Carneiro et al 2016;Itavo et al 2016). The crushed crambe has high lipid content (360-380 g/kg) that can increase the energy density of a diet ( Itavo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the crambe extraction process, by-products (crushed, meal or cakes) are generated with high protein content and great potential for use in ruminant feed to replace traditional protein sources such as soybean meal and cotton (Canova et al 2015;Carneiro et al 2016;Itavo et al 2016). The crushed crambe has high lipid content (360-380 g/kg) that can increase the energy density of a diet ( Itavo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of glucosinolates at high levels represents the primary limitation for the use of crambe in animal feed (Tripathi and Mishra 2007), because the crambe grain has approximately 30-40 g/kg or 90 mol/g of glucosinolates, a toxic level for many organisms (Wallig et al 2002). In ruminants, the toxic products are not produced during digestion (B€ ohme et al 2005); however, reduced intake due to low palatability of crambe by-products is reported (Canova et al 2015;Itavo et al 2016). With this background, the objective of this study was to evaluate the optimum level of crushed crambe to include in the diet of steers as a replacement for soybean meal, measured by the intake and digestibility of nutrients, microbial protein synthesis and nitrogen balance (NB) and ruminal fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Erucic acid is classified as a biodegradable fatty acid. Canova et al (2015), evaluating crushed crambe for use as sheep feed, replaced soybean meal with crambe protein in high-concentrate lamb diets and showed that crambe protein can be used for lambs because it provides a large energy and protein intake with similar protein characteristics to those of soybean meal. Souza et al (2015) completely replaced soybean meal and found no changes in the performance of cows, recommending that soybean meal be replaced with crambe protein in the finishing phase.…”
Section: Introductionmentioning
confidence: 99%
“…A torta de crambe, proveniente da prensagem das sementes para extração do óleo de crambe é utilizada como uma fonte de proteína para a alimentação de bovinos (MizuButi et al, 2011;cAnovA et al, 2015;MendonçA et al, 2015), apresentando índices entre 26 e 28% de proteína bruta (souzA et al, 2009;MizuBiti et al, 2011), o que a torna um provável substituto do farelo de soja. Além da proteína bruta, a torta de crambe é rica em energia, apresentando entre 26 e 33% de extrato etéreo (SouzA et al, 2009;MizuButi et al, 2011).…”
Section: Introductionunclassified